2010
DOI: 10.1590/s0100-06832010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and efficiency of bradyrhizobium strains isolated from soil samples collected from around sesbania virgata roots using cowpea as trap species

Abstract: SUMMARYThe genetic diversity of ten Bradyrhizobium strains was evaluated for tolerance to high temperatures, to different salinity levels and for the efficiency of symbiosis with cowpea plants (Vigna unguiculata (L.) Walp.). Eight of these strains were isolated from nodules that appeared on cowpea after inoculation with suspensions of soil sampled from around the root system of Sesbania virgata (wand riverhemp) in ecosystems of South Minas Gerais. The other two strains used in our analyses as references, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
19
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 30 publications
8
19
1
1
Order By: Relevance
“…Previous studies evaluating bacterial isolates of pigeonpea reported a generally low or intermediate resistance to chloramphenicol and a high susceptibility to kanamycin (Anand and Dogra, 1991;Fernandes et al, 2003;Fernandes Jr. et al, 2012). Other studies also showed that cowpea and common bean rhizobia also presented intermediate to low resistance to kanamycin, as was observed in the present study; however, these isolates presented a low resistance to chloramphenicol (Xavier et al, 1998;Souza et al, 2003;Zilli et al, 2004;Florentino et al, 2010). Souza et al (2003) reported that Rhizobium tropici and E. fredii showed low resistance to chloramphenicol and to kanamycin, indicating that the majority of the bacterial isolates obtained in the present study should not belong to these species or to related groups.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies evaluating bacterial isolates of pigeonpea reported a generally low or intermediate resistance to chloramphenicol and a high susceptibility to kanamycin (Anand and Dogra, 1991;Fernandes et al, 2003;Fernandes Jr. et al, 2012). Other studies also showed that cowpea and common bean rhizobia also presented intermediate to low resistance to kanamycin, as was observed in the present study; however, these isolates presented a low resistance to chloramphenicol (Xavier et al, 1998;Souza et al, 2003;Zilli et al, 2004;Florentino et al, 2010). Souza et al (2003) reported that Rhizobium tropici and E. fredii showed low resistance to chloramphenicol and to kanamycin, indicating that the majority of the bacterial isolates obtained in the present study should not belong to these species or to related groups.…”
Section: Discussionsupporting
confidence: 75%
“…Evaluations of the diversity of rhizobial strains using phenotypic characterization combined with molecular fingerprinting have revealed the great diversity in strains isolated from different Brazilian regions from cowpea (Zilli et al, 2004;Leite et al, 2009;Florentino et al, 2010), yam bean (Freitas et al, 2007), and common bean (Stocco et al, 2008). In the Brazilian Pantanal, studies evaluating the diversity of nodule-forming bacteria with phenotypic and molecular methods remain scarce in spite of the great diversity of the plant cover in the region.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of a wide diversity of microorganisms in a particular soil increases the opportunity for a legume host to find compatible rhizobia. The principle of specific legumerhizobia association is commonly used for the isolation of well adapted and efficient rhizobial strains (Castro-Sowinski et al, 2002;Florentino et al, 2010). Usually trap-plants are used to catch the rhizobial strain with highest performance and the strain is used for the design of new inoculants.…”
Section: Rhizobia: the Master Microbementioning
confidence: 99%
“…: 56302-970, Petrolina-PE, Brasil. ; E-mail: paulo.ivan@embrapa.br metabolism, high temperature and salt tolerance (11,12,17,29).…”
Section: Introductionmentioning
confidence: 99%